INSTITUTIONALS NETWORKS Of KNOWLEDGEMENT VIEWED FROM CONTACTS THEORY - ViIlarroel, Yuli (Cuadernos de Administración, 2008)
This paper assumes a knowledge network as a form or being that reach a certain level of stability and occupies a portio n ofthe space for a certain period oftime. Underthis idea. Systematizes an experience and makes use of concepts and products of the Contacts Theory and the theory ofstratified spaces,to generate a series of thoughts to the process of management of knowledge networks. Join new approaches of thought, such as alife line of a network and his systemic vision in stratified environment, the process of virus detection, the process ofvirus detection, the areas ofuncertainty and orders contact networks that generate executables networks.